‘Amazigh Literary Space’: Intersection and Hybridity across Languages and Media - (:unkn) unknown (My University, 2025)
My contribution will focus on multilingualism and multimedia in the 'Amazigh literary and cinematographic space' (Merolla De l'art, "Amazigh/Berber Literature"). Examining this notion coined in the 1990's (Merolla "Gender and Community") allows us to reflect on ongoing debates regarding North African literatures in postcolonial contexts. It also helps to see that Amazigh/Berber literature solely defined as Amazigh-language production tends to isolate works and performances that engage with multiple languages and literary traditions, cultural intersections, and hybridization in North Africa and its diasporas. The discussion is contextualized within the historical development of what is sometimes referred to as the "North African mosaic" (Boudraa and Krause) and "Tamazgha". Further, to discuss the notion of 'literary and cinematographic space,' I will give examples and introduce some theoretical considerations related to another concept, namely 'literary field.' Finally, by examining the distinctions and convergences among oral performances, writings, cinema and new media productions, this contribution will focus on understanding, and ultimately overcoming, the divisions across disciplinary horizons that had little dialogue between them until recently (Amazigh/Berber Studies, Francophone/Hispanophone … Studies, Postcolonial Studies, World Literature Studies).
Keywords: African Research